New methods for the drawing of the Archaeological Forma Urbis: Bohob’s research in Catania - La Rosa, Laura; Pellegrino, Luigi; Pennisi, Matteo (Technical Annals, 2022)
Nowadays, in the centre of Catania, the several visible archaeologies seem more irrelevant objects than ancient treasures. This is due to fact they are fenced in scattered holes without any common idea. “Bohob”, the group of architects we belong to, is conducting a research in order to address this burning problem by means of a two-pronged approach. On one hand, by the Drawing of the City, a large plan of Catania including all the archaeological ruins representing their integral role in the building of the city and in forcing the shape of the modern town; on the other hand, by the Minimum Projects, consisting of shrines on a citywide scale in which the ruins are enclosed as well as appearing as gems and not as temporary objects in the urban pattern. The core essence of the research is studying the relationship between the archae-ology and the city via an interdisciplinary method based on the brand-new digital forms of representation; starting from considering the ancient as “active part” in the construction of the town and its little fragments as gems mounted in the urban pattern.